Barriers and solutions to stepping down asthma treatment - Nguyen-Ho Lam (Open Journal of Asthma - Peertechz Publications, 2020)
Asthma is a chronic airway disease with two characteristic features: (1) chronic airway inflammation (the most common eosinophilic airway inflammation) and (2) airway hyperresponsiveness (excessive airway constriction by normal triggers) [1]. Management of asthma requires long-term treatment to achieve well-controlled symptoms and prevent the risk of exacerbation in future. Inhaled corticosteroid (ICS) is the mainstay therapy of asthma with strong evidences [2]. Nonetheless it is still the existence of gap in knowledge "what is the most appropriate dose of ICS to treat asthmatic patient?".